Penggabungan Dua Koneksi Internet Service Provider Dengan Teknik Load Balancing Menggunakan Metode Equal Cost Multi Path - Rico Andrian; Malik Abdul Aziz; Muhammad Iqbal (Universitas Lampung, 2021)
Computer networks turn out to be one of the primary needs in life in this era of the globalization. Computer networks are often used simultaneously at certain times so that it can cause overload of bandwidth on the computer network. Overloaded bandwidth can cause disturbances such as networks that feel slower than usual. This study discusses the merger of two service provider internet connections that is done by load balancing techniques using the equal cost multipath method. The stages that will be carried out are analysis, design, simulation or prototyping, implementation, monitoring, and management. The results of the implementation of the application of load balancing techniques with the equal cost multipath method get an increase in the QoS value which can be seen from the test parameters performed namely the average throughput on all computers has increased 0.17%, the average delay for all computers has a decrease in quality of 0.9 milliseconds, the average jitter of all computers has increased the quality of 0.68 milliseconds, and the average packet loss in all computers experienced a 0.58% quality improvement. The configuration of this study was made easier with the help of the web configuration made.